2020
DOI: 10.1007/s40544-019-0343-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Thermal, mechanical, and tribological properties of sodium-montmorillonite-nanoparticle-reinforced polyethersulfone and polytetrafluoroethylene ternary composites

Abstract: Polyethersulfone (PES) and polytetrafluoroethylene (PTFE) blend composites reinforced with sodiummontmorillonite (Na-MMT) nanoparticles were prepared by cold molding and vacuum sintering. The effects of the Na-MMT content on the thermal, nanomechanical, and tribological properties of the Na-MMT/PES/PTFE ternary composites were investigated in detail. The results indicate that at the optimal content, Na-MMT nanoparticles can be uniformly dispersed in the PES/PTFE binary blend composites and generate strong inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, such fillers incur limitations including high grain size, high weight to volume percent, increased friction coefficient, disruption of transition film formation, and corrosion of opposing surfaces [20,21]. To solve these problems, nanosized additives are used to improve the mechanical and physical properties of PTFE composites [20,[22][23][24]. Gao et.…”
Section: Introductionmentioning
confidence: 99%
“…However, such fillers incur limitations including high grain size, high weight to volume percent, increased friction coefficient, disruption of transition film formation, and corrosion of opposing surfaces [20,21]. To solve these problems, nanosized additives are used to improve the mechanical and physical properties of PTFE composites [20,[22][23][24]. Gao et.…”
Section: Introductionmentioning
confidence: 99%
“…The tribological properties of polymers and their composites are attributed to the ability of forming a transfer lm such as polyphenylene [6], polybutylene terephthalate (PBT) [7], ultrahigh molecular weight polyethylene (UMWPE) [8], polyethersulfone (PES) [9]. Pure polymer materials are di cult to apply to actual working conditions due to their high friction coe cient or low wear resistance, thus resulting in the more frequent use of modi ed polymeric materials in practice [10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the response of both compositions to the sliding velocity was exactly contrary for the normal load. The weight, COF, and wear rate of the composite can be decreased with the addition of MMT in the matrix [16,17]. The effect of the grain size and distribution of Ag2s nanoparticles on the mechanical and tribological performance was studied.…”
Section: Introductionmentioning
confidence: 99%